Microstructural, microchemical, and mechanical changes associated with the clinical reuse of two nickel-titanium endodontic instruments - Felipe Augusto Restrepo-Restrepo; Viviana Andrea Holguín-Vásquez; Syldana Julieth Cañas-Jiménez; Paula Andrea Villa-Machado; Sara Ochoa-Soto; Claudia Patricia Ossa-Orozco; Sergio Iván Tobón-Arroyave (Wolters Kluwer Medknow Publications, 2021)
Background: Nickel-titanium (NiTi) instruments have represented a great technological development that enabled endodontists conforming irregular-shaped root canals. Notwithstanding, the repeated use of these instruments may lead to the fracture without any prior visible warning signs. This study aimed to evaluate how multiple clinical instrumentation/sterilization cycles of two NiTi mechanized instruments can affect their microstructural, microchemical, and mechanical characteristics. Materials and Methods: In this observational descriptive study, a total of 140 NiTi instruments, 70 ProTaper Gold® (PTG) and 70 WaveOne Gold® (WOG) were analyzed. For each brand system, instruments were evaluated in the as-received condition (n = 10) and after one (n = 20), two (n = 20), and three (n = 20) instrumentation/sterilization cycles. Intraoperative instrumentation parameters were recorded for all used instruments. Afterward, the files were examined using scanning electron microscopy and energy-dispersive X-ray microanalysis. All of the instruments were tensile-fatigue tested until rupture in order to calculate the mechanical tensile strength and the maximum elongation percentage for the samples. Statistical analysis was completed using Chi-square, Kruskal-Wallis H-, or Mann-Whitney U-tests with a statistical significance set at P < 0.05. Results: Significant increasing changes in surface topography (P < 0.05, Chi-square test) and chemical composition (P < 0.05, Kruskal-Wallis H-test) in both brand systems through instrumentation/sterilization cycles were detected. In addition, values of mechanical tensile strength and maximum elongation percentage increased significantly through instrumentation/sterilization cycles in the PTG group, whereas only the median values of mechanical tensile strength increased significantly in the WOG group (all P < 0.01, Kruskal-Wallis H-test). Conclusion: Although multiple instrumentation/sterilization cycles may render NiTi instruments more flexible and fatigue resistant, the significant changes detected in their surface topography and chemical composition should preclude their repeated clinical use in the routine endodontic practice as prevention for breakage.